Práticas de condução de discussões matemáticas: Os casos de dois professores - Rodrigues, Cátia (2017)
In this paper we analyze the learning dynamics of a group of five middle school teachers that took place in a lesson study during the elaboration and analysis of a diagnostic task. Specifically, we aim to analyze the changes that occurred in the teachers’ didactical knowledge, notably in their curriculum knowledge, knowledge of students and in their learning processes, and knowledge of teaching practice. Data were collected by participant observation, with audio recording of the sessions, collection of participants’ written documents, and by making a research journal. The results suggest that the elaboration and analysis of a diagnostic task during the lesson study, through a reflexive process, gave the teachers na opportunity to develop didactical knowledge about curriculum guidelines for the specific content, students’ thinking, tasks, and the role of diferente representations for learning rational numbers. This work also allowed the teachers to change their knowledge about the students and, more specifically, about their real capacity, leading the teachers to value the positive aspects of their students’ solutions and not only attend to their difficulties.